First students graduated from the Women’s Medical Institute (to the 120th anniversary of the event) - A. A. Zhuravlyov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
The article describes the history of the first students enrolled and graduated from the St. Petersburg Women’s Medical Institute. The article describes how public organizations and various individuals helped women receive higher medical education. How Russian public reacted to the first graduation of students of the Institute. The fate of two graduates of 1902 is presented, based upon archival materials.